A REVIEW OF THE GENUS SYPHACIA (NEMATODA: OXYURIDAE) FROM MURINE RODENTS IN SOUTHEAST ASIA TO AUSTRALIA WITH SPECIAL REFERENCES TO INDONESIA - Kartika Dewi; Hideo Hasegawa; Mitsuhiko Asakawa (Treubia, 2016)
The pinworms of the genus Syphacia are of special interest because they have coevolutionary relationships with their murine rodent hosts. From Southeast Asia to Australia, 21 species in four subgenera have been recorded, two species of these are endemic to Sulawesi. Their biogeographical distribution and dispersal processes are discussed herein. The species composition of Syphacia seems to be mosaic among the islands, especially in Wallacea. Based on the morphological characteristics of the cephalic ends, the species of the subgenus Syphacia are divided into three lineages with square (S), round (R) and laterallyelongated (LE) cephalic shapes. The LE type is assumed to be primitive and the S and R types are derived from the LE type as shown by a molecular phylogeny based on 28S rDNA previously. This assumption was supported by the fact that the old endemics murines in the regions studied mostly harboured Syphacia with LE type A hypothesis on the formation of the host-parasite relationships between murines and subgenus Syphacia in the areas is presented. A key to Syphacia species recorded is also provided